Elimination of Granulocytic Myeloid‐Derived Suppressor Cells in Lupus‐Prone Mice Linked to Reactive Oxygen Species–Dependent Extracellular Trap Formation. Issue 2 (February 2016) - Vlachou, Katerina; Mintzas, Konstantinos; Glymenaki, Maria; Ioannou, Marianna; Papadaki, Garyfalia; Bertsias, George K.; Sidiropoulos, Prodromos; Boumpas, Dimitrios T.; Verginis, Panayotis
Abstract : Objective: Emerging evidence supports a crucial role of myeloid‐derived suppressor cells (MDSCs) in the regulation of autoimmune diseases. However, their role in systemic lupus erythematosus (SLE) remains unknown. This study sought to address the role of MDSCs in the pathogenesis of SLE. Methods: MDSCs from (NZB × NZW)F1 lupus‐prone mice were assessed for phenotype by flow cytometry, and the function of MDSCs was analyzed by in vitro T cell proliferation assay and real‐time quantitative polymerase chain reaction. Extracellular trap (ET) formation was evaluated by immunofluorescence and confocal microscopy. The production of reactive oxygen species (ROS) by Ly‐6G+ cells was determined by fluorescence‐activated cell sorting analysis. Results: Expansion of MDSCs was impaired and the function of MDSCs was defective in the lymphoid organs of (NZB × NZW)F1 lupus‐prone mice with established disease, in which involvement of predominantly the granulocytic MDSC (G‐MDSC) cell subset was observed. More specifically, the results showed that increased elimination of G‐MDSCs, driven by the inflammatory milieu of lupus, could be attributed to ET formation, and that cytokines, such as interferon‐α (IFNα), IFNγ, and interleukin‐6, play a role in this process. Induction of ET release by G‐MDSCs was mediated by the production of ROS, since inhibition of ROS generation significantly reduced ET release. Conclusion: Collectively, the results of this study reveal that elimination of a crucial regulatory immune cell subset is a feature of the SLE microenvironment. These findings provide new insights into the pathogenetic mechanisms of the disease.